2005
DOI: 10.1038/sj.bjc.6602634
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of haemoglobin beta (HBB) gene in anaplastic thyroid cancer and recovory of its expression inhibits cell growth

Abstract: Anaplastic thyroid cancer (ATC) is one of the most fulminant and foetal diseases in human malignancies. However, the genetic alterations and carcinogenic mechanisms of ATC are still unclear. Recently, we investigated the gene expression profile of 11 anaplastic thyroid cancer cell lines (ACL) and significant decreased expression of haemoglobin beta (HBB) gene in ACL. Haemoglobin beta is located at 11p15.5, where loss of heterozygosity (LOH) was reported in various kinds of cancers, including ATC, and it has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 28 publications
0
34
0
2
Order By: Relevance
“…HBB was found to be significantly downregulated in 11 anaplastic thyroid cancer cell lines, and a cell proliferation assay suggested that HBB might be a novel TSG (41). Analysis of primary and post-treatment samples (12 tumor and eight normal) by the Affymetrix platform (HG U133 plus 2) identified 119 genes as differentially regulated in recurrent tumors, of which HBB alone, and collagen, type V, α1 (COL5A1) and HBB in combination, have the best predictive power for treatment response in patients with oral tongue cancer (42).…”
Section: Discussionmentioning
confidence: 99%
“…HBB was found to be significantly downregulated in 11 anaplastic thyroid cancer cell lines, and a cell proliferation assay suggested that HBB might be a novel TSG (41). Analysis of primary and post-treatment samples (12 tumor and eight normal) by the Affymetrix platform (HG U133 plus 2) identified 119 genes as differentially regulated in recurrent tumors, of which HBB alone, and collagen, type V, α1 (COL5A1) and HBB in combination, have the best predictive power for treatment response in patients with oral tongue cancer (42).…”
Section: Discussionmentioning
confidence: 99%
“…To adjust the amount of transcribed cDNA, GAPDH was selected as an internal control and SQ-PCR was performed as previously described (Onda et al 2005); the primer sequences for GAPDH were 5¢-ggaaggtgaaggtcggagt-3¢ (forward) and 5¢-tgggtggaatcatattggaa-3¢ (reverse). After adjustment of concentrations, SQ-PCR experiments for TMEM34 were performed using primers 5¢-ggcttggtttattgctggaa-3¢ (forward) and 5¢-gtgtgggcccaatattcatc-3¢ (reverse); all primers were designed with primer 3 (http://www-genome.wi.mit.edu/cgi-bin/primer/primer3_www.cgi) after sequence information was obtained from NCBI GenBank (http://www.ncbi.nlm.nih.gov/).…”
Section: Specimens For Normal Controlmentioning
confidence: 99%
“…Q-PCR experiments were performed with an ABI PRISM 7700 Sequence Detector (Applied Biosystems, Foster City, CA, USA) according to the comparativethreshold (Ct) cycle method, as previously described (Onda et al 2005). All quantitative RT-PCR products were visualized on a 2% agarose gel to ensure a single product.…”
Section: Quantitative Rt-pcr (Q-pcr)mentioning
confidence: 99%
See 2 more Smart Citations